Biochar Reinforced Polyvinyl Alcohol /Corn Starch Biocomposites - Terzioğlu, Pınar; Parın, Fatma Nur (My University, 2020)
The utilization of biochar in polymer composites can be considered as a sustainable approach that provide valorization of a waste to a value-added material and at the same time diminish biowaste in a smart way.This study is focused on the evaluation of biochar as a filler in polyvinyl alcohol /corn starch composites. The composites were prepared via solution mixing and castingmethod using citric acid as a plasticizer and glutaraldehyde as a cross-linker. Distribution of biochar in the PVA/starch matrix was evaluated by optical microscopy. The structural features of composites were characterized using FTIR spectroscopy. Effectsof biochar loading ratio (0-12 wt%) on the thermal stability of the PVA/starch blends were determined bydifferentialscanning calorimetry andthermogravimetric analyses. The decomposition temperatures of the PVA/starch/biochar composites decreased in comparison to PVA/starch composites.
Keywords: [No Keywords]